STANDARDS: A DIALOGUE. - Kohler, E. L. (The Accounting Review, 1935)
Abstract The article focuses on standards for accounting. A good deal has been said recently about standards for accountants. The book Financial Reports for Colleges and Universities reflects probably the first attempt in the history of accounting to produce a coordinated, closely integrated textbook of standards, not withstanding the fact that it covers a specialized field. But what about the hundreds of uniform systems of accounts that have been produced since pioneering in railway accounting? That's a fair question. There have been many uniform systems of accounts put out by our public-service commissions, the I. C. C., and a pretty good number of trade associations. Most of them have dwelt extensively on account classifications and how and what to debit and credit. Most of them include provisions for some sort of financial statements. At this stage in the development of accounting, it would be difficult to frame definitions that everybody would agree to. It's the courageous effort to lay down a reasonable set of standards that is needed.